P072 Melanocortin MC3 and MC5 receptors expression is different according to colonic disease activity in Crohn's Disease and Ulcerative Colitis biopsies: results from an immunohistochemical observational study. (21st January 2022) - Gravina MD, A G; Panarese, I; Trotta, M C; D'Amico, M; Pellegrino, R; Ferraraccio, F; Galdiero, M; Alfano, R; Loguercio, C; Romano, M; Grieco, P; Federico, A
Abstract: Background: MC3-R and MC5-R receptors belong to the complex melanocortin system, which has shown a strong immunomodulatory activity in several studies. Data on the role of these receptors in relation to inflammatory bowel disease are still missing and not fully elucidated. In this observational study we wanted to evaluate the expression profile of them in the colonic mucosa of Crohn's Disease and Ulcerative Colitis patients both in the tracts directly affected by the disease activity and in the tracts spared. Methods: We conducted on colonic biopsies of patients with histological diagnosis of inflammatory bowel disease immunohistochemical analyses in order to assess the degree of expression of MC3-R and MC5-R. Biopsies were performed on both the traits with macroscopic signs of inflammation and the macroscopically normal traits to assess whether the expression of the two receptors was different in relation to disease activity. Results: In both Crohn's disease and ulcerative colitis diseased tracts MC3-R (CD: +7.7 fold vs normal mucosa, P < 0.01; UC: +5.6 fold vs normal mucosa, P < 0.01) and MC5-R (CD: +5.5 fold vs normal mucosa, P < 0.01; UC: +8.1 fold vs normal mucosa, P < 0.01) were significantly increased compared to healthy mucosa. Conclusion: MC3-R and MC5-R are expressed in the colon of patients with Crohn's Disease and Ulcerative Colitis. In addition, expression is different with a higher degree of expression in the traits most affected by disease activity in both Crohn's Disease and Ulcerative Colitis providing a potential use of these receptors in inflammatory bowel diseases pharmacology.